Urgensi Psikologi dalam Pendidikan - Roni Putra; Muharrama Trifiriani; Yuri Indri Yani (IJIP : Indonesian Journal of Islamic Psychology, 2021)
Abstract Psychology is a science that aims to understand humans, with the aim of being able to treat them more appropriately. Therefore, for every educator, the psychological knowledge of students in the educational process is necessary and important. Therefore, every educator needs to understand the science of educational psychology. Given that everyone has to carry out educational activities at the same time, basically everyone needs educational psychology. The method used in this scientific article uses the review literature. The contribution of psychology to education: the contribution of educational psychology to curriculum development, the contribution of educational psychology to the learning system, the contribution of educational psychology to the assessment system. AbstrakPsikologi adalah ilmu yang bertujuan untuk memahami manusia, dengan tujuan agar dapat memperlakukannya dengan lebih tepat. Oleh karena itu, bagi setiap pendidik pengetahuan psikologis peserta didik dalam proses pendidikan merupakan hal yang perlu dan penting. Oleh karena itu, setiap pendidik perlu memahami ilmu tentang psikologi pendidikan. Mengingat setiap orang harus melaksanakan kegiatan pendidikan pada waktu yang bersamaan, maka pada dasarnya setiap orang membutuhkan psikologi pendidikan. Metode yang digunakan dalam artikel ilimiah ini menggunakan literatur riview. Kontribusi psikologi terhadap pendidikan: kontribusi psikologi pendidikan terhadap pengembangan kurikulum, kontribusi psikologi pendidikan terhadap sistem pembelajaran, kontribusi psikologi pendidikan terhadap sistem penilaian.